The Challenges of government in Pakistan and future possibilities - Gholam Ali Chegnizadeh (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2006)
This paper elaborates a new approach to the recent changes in Pakistan. Reasoning presented in this article signify that the nature of recent changes and challenges is distinguished from all the periods after the independence of this country. The proponing of Islamic forces new demands (resulting from international, regional and national changes), has confronted the foundation of power structure in Pakistan with a new challenge. Doubtless, the certain effects of this process would be the redefining of religion’s role in politics. Having suggested this proposition, it can be claimed that the state formation’s trajectory in Pakistan has lost it’s logic, external and internal sources after the independence and confronted with a serious crisis. Presently, two alternatives, Islam and democracy (emphasizing the separatism of religion from politics), have initiated a new challenge for affecting the new state formation process in Pakistan. It can be inferred from the above that the existing theoretical and practical ambiguities and uncertainties in Pakistan’s political society that results from clashes and different confronting perceptions in state formation domain in the country, have greatly changed the nature of security issues in this country and differentiated the conflict and cooperation pattern from the past.